KAJIAN NARASI PASTORAL PADA KUMPULAN PUSI JALAN HATI, JALAN SAMUDRA KARYA D. ZAWAWI IMRON DAN IMPLIKASINYA UNTUK PEMBELAJARAN SASTRA DI SMA - Abdul Azis; Arip Senjaya; Ahmad Supena (Sasando, 2025)
This research departs from the ecocentric paradigm in ecocritical studies which aims to describe the elements of pastoral values ​​in the poetry collection "Jalan Hati, Jalan Samudra" by D. Zawawi Imron. Ecocriticism guides us to see the ecological views contained in literary works. The natural environment or the relationship between natural elements experiences textualization in text discourse, so ecocriticism must focus on the textual strategies of literary texts in conveying ecological messages about how humans interact with the organic world around them. This research method is a qualitative method. This research identifies the pastoral elements of Terry Gifford, namely bucolic, arcadia construction, and the discourse of retreat and return and how these have implications for literary learning. The results of this research found eight data of bucolic elements, fifty-three data of arcadia construction elements in the form of idylls, eighteen data of arcadia construction elements in the form of nostalgia, twenty-three data of arcadia construction elements in the form of georgic, and twenty-three data of retreat and return discourse elements. eighteen data. The results of this research are also worthy of being used as teaching material for literature learning.